Penguasaan Bahasa Inggris Melalui Extensive Reading - Syamsiah Depalina siregar (Universitas Muhammadiyah Tapanuli Selatan, 2016)
Even though there is no representative data reporting the profile of Indonesian students’ proficiency in English, it seems that English teaching program has been largely unsuccessful. Factually, most of high school graduates just had average reading vocabulary of 1000 words, a number considered too small. This phenomenon needs an appropriate solution. Extensive Reading (ER) may be the answer. Why? Because it can, with “easy and interesting” strategy, motivate students’ interest in reading, increase their language acquisition, and eliminate their negative predisposition on English as either difficult language or bored lesson.